Elementary School Teachers’ Readiness in Teaching Technology-based Literacy - Padmadewi, Ni Nyoman; Artini, Luh Putu; Ratminingsih, Ni Made; Trika Adi Ana, I Ketut (International Journal of Elementary Education, 2023)
The Independent Curriculum requires teachers to have the ability to use technology in the learning process and improve students' literacy skills. However, there are still many teachers who experience difficulties in using technology and increasing student literacy. For this reason, this study aims to identify the effect of multimodal training on increasing teacher readiness to implement technology-based literacy learning. This research is a mixed-method study with a concurrent triangulation design involving 24 English teachers. Methods of data collection through questionnaires, interviews and observation. Data were analyzed quantitatively and qualitatively. This study found that teacher readiness in implementing technology-based literacy learning increased significantly after multimodal training. These results are supported by qualitative data showing that teachers feel better prepared to teach literacy in English. This study also found that teachers positively perceive multimodal training. It can be concluded that multimodal training positively affects teacher readiness in implementing technology-based English literacy learning. Thus, implementing multimodal training can be used as a solution to solve teacher problems in conducting the teaching and learning process using technology and increasing student literacy.